A comparative study on condition of hypertensive and non-hypertensive patients with dental implant success and survival: 15 years follow ups - Khan, Abdullah Al Mamun; Zahan, Nasrin Parvin (International Surgery Journal, 2025)
Background: The study evaluates the success and survival of dental implants in hypertensive and non-hypertensive patients over a 15-year follow-up period. Hypertension may affect osseointegration and implant longevity, necessitating careful assessment of its impact on implant success. Methods: This comparative study was conducted at Banasree Dental and Implant Center and German Dental and Implant Center, Dhaka, Bangladesh. A total of 109 patients were initially selected, but 19 were excluded due to loss to follow-up. Finally, 90 patients (67 females, 23 males, 45 in each group) were included, receiving a total of 257 implants (135 implants in maxilla and 122 implants in mandible), including guided bone regeneration (GBR) and sinus elevation. Participants aged 35 to 70 years underwent implant surgeries in 2009, with follow-ups until 2024. Results: Marginal bone loss ranged from 0.5 mm to 2.0 mm, which is within the normal limit. All implants (100%) remained functional, with no significant difference in outcomes between hypertensive and non-hypertensive groups. This suggests that well-integrated implants can achieve long-term survival even in uncontrolled hypertensive patients. Conclusions: With careful planning, proper blood pressure management, and close collaboration between healthcare providers, dental implants can be a durable and successful tooth replacement option for hypertensive patients. Ensuring optimal preoperative, intraoperative, and postoperative care is crucial for long-term implant stability, regardless of hypertension status.